UJI DAYA HAMBAT EKSTRAK BAWANG DAYAK (Eleutherine palmifolia (L.) Merr.) TERHADAP BAKTERI Salmonella parayphi - Nor Aini Aida; Febri Nur Ngazizah; Miftachul Sobirin; Riky Riky (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Dayak onions (Eleutherine palmifolia (L.) Merr.) Is one of the natural ingredients which is often used for medicine in Kalimantan. E. palmifolia used for treatment because it contains secondary metabolite compounds that have potential as antibacterial. Such as phenolic compounds, flavonoids, alkaloids, saponins, tannins and glycosides which are included in polar compounds. This study aims to determine the effect of ethanol extract 70% E. palmifolia against bacteria Salmonella paratyphi with the extraction method maceration. S. paratyphi is a bacterial pathogen against humans whose habitat is in the digestive tract. This research was conducted to test the extract's antibacterial activity with gradient concentration of 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, and 60 mg / mL and chloramphenicol as a positive control and sterile aquadest as a negative control. The antibacterial test method used is diffusion method with 5 repetitions. Our results showed that E. palmifolia extract could inhibit S. paratyphi growth as evidenced by the presence of an inhibition zone that is formed around paper disk on media with concentration 20 mg / mL, 30 mg / mL, 40 mg / mL, 50 mg / mL, and 60 mg / mL. Where the average diameter of the inhibition zone was 6.6 mm, 7.4 mm, 8.8 mm, 9.9 mm, respectively fall into the category of ineffective inhibition and 11 mm is in the weak category. Based on the research that has been done, it was found that there was an effect of giving E. palmifolia extract on the growth of S. paratyphi bacteria but there was no significant difference based on the one way ANOVA test.